Social Sector in a Decentralized Economy India in the Era of Globalization - Chakraborty, Pinaki (Social Sciences, 2017)
This book is an analytical examination of financing and public service delivery challenges in a decentralized framework. In addition, it provides critical insights into the effectiveness of public expenditure, through benefit incidence analysis of education and healthcare services in India.